THE URGENCY OF LEGISLATION TO CHANGE THE CONSUMER AND BUSINESS PROTECTION LAW NUMBER 8 OF 1999 FROM THE PERSPECTIVE OF QUR'AN AND HADITH VALUES - kurnianti, Lusia nia; Marhumah, Marhumah (Faculty of Law, Universitas Pekalongan, 2024)
ABSTRACTThe role of business actors in the process of marketing goods and services is a very sensitive topic to discuss. Talking about international, national and local markets, this is a multi-complex problem. One of them is legal protection for consumers of goods and services. The issue of consumer protection was regulated in 1999, but following the development of the flow of free trade, of course this must continue to be progressive in order to carry out observations to make adjustments to consumer problems which in fact concern human benefit and safety, of course. The legal protection policy for consumers and business actors is a struggle that is still far from expectations, a struggle since 2008, has not yet produced results to date. The fact that no changes have been made to this law is proof and fact of the reluctance of the legislative bodies and the participation of the government executive who should be pushing to the maximum extent to make efforts to change these regulations as an urgent matter. The struggles of consumer observers and business actors, both from consumer observer institutions and academics, do not have enough power to voice the aspirations of the people as consumers. Various perspectives from the perspective of positive law have been studied so far, and the author on this occasion would like to re-touch the Islamic conscience of Muslims who will of course be moved to look again at the values of the Al-Quran and Hadith